3-(4-Hydroxyphenyl)propionic acid, a major microbial metabolite of procyanidin A2, shows similar suppression of macrophage foam cell formation as its parent molecule - Zhang, Yu-Ying; Li, Xiao-Le; Li, Tong-Yun; Li, Mei-Ying; Huang, Ri-Ming; Li, Wu; Yang, Rui-Li (RSC advances, 2018)
The effect of procyanidin A2 (PCA2) and its major colonic metabolite 3-(4-hydroxyphenyl)propionic acid (HPPA) on the suppression of macrophage foam cell formation, and underlying mechanism, were investigated for the first time. The results showed that 12.5 μg mL −1 PCA2 and HPPA significantly reduced cellular lipid accumulation and inhibited foam cell formation. HPPA promoted macrophage cholesterol efflux by up-regulating mRNA expressions of ABCA1 and SR-B1, while PCA2 significantly increased SR-B1 and LXR-α mRNA expression levels. Moreover, PCA2 and HPPA significantly lowered the elevated levels of CD36 mRNA expression in ox-LDL-treated macrophage cells. Besides these, the ox-LDL-induced cellular oxidative stress and inflammation was also restricted by PCA2 and HPPA treatment via nuclear factor kappa-B pathways. In conclusion, PCA2 and its major microbial metabolite, HPPA, inhibited the conversion of macrophage into foam cells via regulating cellular lipid metabolism and suppressing cellular oxidative stress and inflammation. PCA2 and its major microbial metabolite HPPA inhibited macrophage foam cell formation, which may be due to regulating ABCA1, SR-B1 and CD36 expression, and restricted cellular oxidative stress and inflammation via NF-κB pathway.